Butterfly diversity and conservation implications in Real, Quezon, Philippines - EUNICE LOIS O. CABARDO; ELEANOR S. AUSTRIA; JULIUS JOHN DP. SALAMANES (Society for Indonesian Biodiversity, 2025)
Abstract. Cabardo ELO, Austria ES, Salamanes JJDP. 2025. Butterfly diversity and conservation implications in Real, Quezon, Philippines. Biodiversitas 26: 4363-4373. Butterflies are key bioindicators of environmental health, yet systematic studies on lowland butterfly assemblages in the Philippines are scarce, leaving a crucial gap in biodiversity knowledge and conservation planning. This study aimed to document the diversity, abundance, and habitat associations of butterflies in Brgy. Malapad, Real, Quezon (a lowland barangay within the Sierra Madre Biodiversity Corridor) and to assess their conservation implications. Sampling was conducted from March to June 2024 in two distinct sites: a riparian zone near Nonok Falls and a secondary forest. Using Pollard Walk transects, bait traps, and opportunistic netting, 103 individuals representing 27 species, 22 genera, and 5 families were recorded. Nymphalidae was the most dominant family in terms of species richness and abundance. The riparian zone showed notably higher species richness (20 species), diversity (H?: 2.8115, 1?D: 0.9486), and evenness (J?: 0.9385) than the secondary forest with 13 species, diversity (H?: 2.1630, 1?D: 0.8667), and evenness (J?: 0.7346). Community composition between the two habitats differed substantially, as indicated by a Bray-Curtis dissimilarity index of 0.748. This dissimilarity was statistically supported by a significant Hutcheson t-test (t: 4.444), confirming a marked difference in butterfly diversity between sites. One species, Notocrypta paralysos, was classified as Vulnerable, while five species were endemic to the Philippines. The presence of both endemic and threatened species highlights the urgent need to prioritize lowland habitats in regional conservation strategies. These findings underscore the conservation importance of lowland ecosystems and highlight the need to integrate butterfly diversity data into local conservation planning. This study offers a vital baseline for biodiversity monitoring and supports sustainable land-use and community-based habitat management efforts.